2023
DOI: 10.1111/jre.13215
|View full text |Cite
|
Sign up to set email alerts
|

Identifying genes for regulating osteogenic differentiation of human periodontal ligament stem cells in inflammatory environments by bioinformatics analysis

Qing Wang,
Xiaojie Yang,
Xuechun Wang
et al.

Abstract: Background and ObjectivesPeriodontitis is an immuno‐inflammatory disease caused by dental plaque biofilms and inflammations. The regeneration of bone tissue in inflammatory environment is of great significance for the treatment of periodontal disease, but the specific molecular mechanism of bone formation in periodontitis still needs further exploration. The objective of this study was to identify key osteogenesis‐related genes (ORGs) in periodontitis.MethodsWe used two datasets from the Gene Expression Omnibu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The association of FGF-2 with heparin significantly decreases the degradation of FGF-2 and greatly enhances its mitogenic activity. Additionally, heparin sulfate proteoglycans act as cofactors in the interactions between FGF2 and FGF receptors, facilitating the activation of downstream signaling pathways [55][56][57]. In general, clinical data substantiates the safety and effectiveness of employing FGF-2 in the treatment of intraosseous defects in periodontal conditions.…”
Section: Fibroblast-derived Growth Factor (Fgf)mentioning
confidence: 91%
See 1 more Smart Citation
“…The association of FGF-2 with heparin significantly decreases the degradation of FGF-2 and greatly enhances its mitogenic activity. Additionally, heparin sulfate proteoglycans act as cofactors in the interactions between FGF2 and FGF receptors, facilitating the activation of downstream signaling pathways [55][56][57]. In general, clinical data substantiates the safety and effectiveness of employing FGF-2 in the treatment of intraosseous defects in periodontal conditions.…”
Section: Fibroblast-derived Growth Factor (Fgf)mentioning
confidence: 91%
“…This product incorporates β-tricalcium phosphate as a scaffold [50,51,55]. Residing within the ζ-granules of platelets and discharged upon activation, PDGF has been demonstrated to stimulate DNA synthesis, chemotaxis, and the synthesis of collagen and glycosaminoglycans in fibroblasts [56][57][58]. Laboratory analyses conducted in vitro have shown that PDGF significantly enhances the expression of stem cell markers and promotes the proliferation of mesenchymal stem cells (MSCs) isolated from PDL tissues [59].…”
Section: Platelet-derived Growth Factor (Pdgf)mentioning
confidence: 99%
“…A recent study assessed periodontal regenerative approaches in animal models, observing that mesenchymal stem cells used alone or mixed with other biomaterials, such as bovine bone, beta-tricalcium phosphate, or platelet-rich plasma, offered better regenerative outcomes than those of the group with biomaterials alone [42]. Most preclinical studies have indeed supported the biological rationale of employing MSCs to promote osteoinduction and tenogenesis, while simultaneously decreasing inflammation [26,[43][44][45].…”
Section: Introductionmentioning
confidence: 99%